Urgency of Islamization of Science By Ismail Raji Al Faruqi in Responding to The Challenges of Contemporary Social Phenomena - Nuryanti, Nuryanti; Helmiati, Helmiati; Nazir, M (Jurnal Ilmiah Global Education, 2025)
The main purpose of this study is to analyze the concept of science integration developed by al-Faruqi, understand the factors behind the emergence of this idea, and explore its implementation and relevance in the world of Islamic education today. This research also aims to compare al-Faruqi's ideas with other Muslim thinkers in order to gain a more comprehensive understanding of the integration of science in Islam. This study uses a qualitative approach with a literature study method. Data was collected from primary sources in the form of al-Faruqi's works, such as Islamization of Knowledge , as well as various secondary literature that discussed his thoughts. The analysis is carried out in a descriptive-analytical manner with a critical approach to the concept of Islamization of the knowledge he developed, and examines how this concept can be applied in the modern Islamic education system. The results of the study show that the concept of Islamization of science introduced by al-Faruqi aims to eliminate the dichotomy between religious science and modern science by making Islam the basis of epistemology in all scientific fields. Al-Faruqi emphasized that the Islamization of science is not just adding religious elements to secular science, but reconstructing science based on a comprehensive Islamic perspective. This concept has been implemented in various Islamic educational institutions, although it still faces challenges in its widespread application. By understanding the concept of al-Faruqi more deeply, it is hoped that Muslims can develop a more integrative and oriented education system that is oriented authentically towards Islamic values.